PENGARUH BAGI HASIL DEPOSITO MUDHARABAH, SUKU BUNGA BERJANGKA BANK INDONESIA DAN INFLASI TERHADAP JUMLAH DEPOSITO MUDHARABAH PT. BANK NEGARA INDONESIA (BNI) SYARIAH - Sri Rahayu; Rahmadani Siregar (Universitas Islam Islam Sumatera Utara, 2018)
The development of sharia banking is driven by the existence of some communities to perform banking transactions or economic activities in general. This kind of bank is in line with the values and principles of sharia, especially free from usury, as well as the superiority of operational systems and its products which are stressing on the importance of morality, justice and transparency in the operational activities. Mudharabah deposit is one form of Islamic banking financing product which is a fund investment based on mudharabah contract or other contracts that are not contradictory to sharia principles. The withdrawal can only be done at certain time based on contract between sharia bank depositors or Syariah Business Unit. The purpose of this research is to analyze the effect of profit sharing rate on mudharabah deposit, 1 month Bank Indonesia interest rate, and inflation to mudharabah deposit amount. This research was conducted at BNI Syariah. The research method used associative approach while the technique of data analysis using multiple linear regression analysis. The result of analysis shows that simultaneously variable of profit sharing amount of mudharabah deposit, interest rate of Bank Indonesia 1 month, and inflation have significant effect to mudharabah deposit amount. However, partially, only the profit sharing rate of mudharabah and inflation has significant effect on the number of mudharabah deposits. This is because of the customers motive in placing their funds in shariah banks are still influenced by the profit orientation.